Association between Pre-, Intra-, and Postpartum Risk Factors with Developmental Delay in Infants: A Case-Control Study - Fatemeh Jalali; Gholamreza Bazmandegan; Abbas Fatehi; Nazanin Jalali; Marzieh Esmaeli Dahaki; Zahra Kamiab (Iranian Journal of Neonatology)
Background: Developmental delay (DD) is an important problem in children, and recognizing the factors affecting it is very critical in diagnosing and improving development. The aim of this study was to investigate the relationship between pre-, intra-, and postpartum risk factors with DD in infants. Methods: In this case-control study, 110 infants with DD and 110 healthy infants from health centers in Rafsanjan were studied. At 12 months, the developmental status of infants was assessed using the ages and stages questionnaire (ASQ) at the age of 12 months. Information on risk factors was collected in a researcher-made checklist. Results: The mean age of mothers during pregnancy was 28.83 ± 5.27 years in the case group and 29.21 ± 4.86 years in the control group (P = 0.57). Frequency of diploma or less education (P <0.001), rural residence (P<0.001), preterm infants (P = 0.045), and pathological jaundice (P = 0.027) were significantly higher in the case group. There was an association between DD with maternal education level (OR = 2.745, 95% CI: 1.587-4.747), number of pregnancies (OR = 1.494, 95% CI: 1.156-1.930), and history of pathological neonatal jaundice (OR = 3.963, 95% CI: 1.074-14.662). Conclusion: According to the results of the study, Low maternal education, more pregnancies, and a history of pathological neonatal jaundice were factors affecting DD. It is recommended that more attention be paid to risk factors to prevent future adverse events.